Palladium‐Catalyzed Annulation of Aryltriazoles and Arylisoxazoles with Alkynes - Yuan, Hairui; Wang, Min; Xu, Zhenghu; Gao, Hongyin (Advanced synthesis & catalysis, 2019)
We developed herein a palladium‐catalyzed annulation of aryltriazoles and arylisoxazoles with internal alkynes via C−H bond activation process. 4,5‐disubstituted‐3H‐naphtho[1,2‐d][1,2,3]triazoles and 4,5‐disubstituted‐naphtho[2,1‐d]isoxazoles could be afforded in good yields, respectively. The starting materials are readily available and the scope and applications of this transformation were explored. The reaction offers a practical approach to naphthalene fused heterocycles.